Dexmedetomidine prevent postoperative nausea and vomiting on patients during general anesthesia: A PRISMA-compliant meta analysis of randomized controlled trials. Issue 1 (January 2017) - Jin, Shenhui; Liang, Dong Dong; Chen, Chengyu; Zhang, Minyuan; Wang, Junlu
Abstract: Background: Postoperative nausea and vomiting (PONV) is a frequent complication in postoperative period. The aim of this article was to evaluate the effect of dexmedetomidine on PONV. Method: RevMan 5.3 software was applied for performing statistic analysis. Twenty-four trials with 2046 patients were included. Results: The PONV of the dexmedetomidine group was significantly lower compared with the placebo group (0.56, 95% CI: 0.46, 0.69). Subgroup analysis further confirmed the effect of dexmedetomidine (irrespective of administration mode) ( P < 0.00001). Perioperative fentanyl consumption in dexmedetomidine group were also reduced significantly ( P < 0.00001). Whereas, side effects such as bradycardia, hypotension increased in dexmedetomidine group (especially in loading dose mode and loading dose plus continuous infusion mode). Conclusions: Dexmedetomidine administrated in continuous infusion mode has the advantage to prevent PONV as well as reduce side effects such as bradycardia and hypotension. Abstract : Supplemental Digital Content is available in the text